Pengaruh Kepemimpinan dan Iklim Sekolah terhadap Sekolah Efektif di SMP Negeri Kecamatan Pulung Kabupaten Ponorogo Tahun Pelajaran 2021/2022 - Ainul Nurhayati Istiqomah; Umi Rohmah (Excelencia: Journal of Islamic Education & Management, 2022)
Effective school implementation is used as a benchmark to find out how far the school has achieved the planned goals. Based on the observation that the creation of effective schools it has not been fully implemented, as evidenced by the lack of supervision by the principal towards teachers and students and school regulations being violated. Effective school implementation is influenced by many factors including leadership factors and school climate factors. The purpose of the study was to analyze the influence of leadership and school climate on effective schools in SMP Negeri Pulung District, Ponorogo Regency for the 2021/2022 academic year, either partially or simultaneously. This research is a quantitative research with Ex Post Facto design. Data collection techniques using questionnaires, documentation, and observation. The research population was 71 teachers. The data analysis technique used simple linear regression analysis and multiple linear regression with the help of IBM SPSS 25. The results showed: (1) there was a positive and significant effect of leadership on effective schools with a value of tcount(7,360) > ttable(1,995), an effect of 44%; (2) there is a positive and significant effect of school climate on effective schools with a value of tcount(6.779) > ttable(1.995), an effect of 40%; and (3) there is a positive and significant effect together with leadership and school climate on effective schools with a value of Fcount(4.601)>Ftable(2.74), an effect of 55% on effective schools.